Drawing in the project: image and object - Magalhães, Graça Maria Alves dos Santos (2014)
This text occurs from the interpretation in progress about the relationships between design and drawing. We intend to contribute to the study of the configuration of the object of design through the symbolic image implicit in the drawing and of the drawing allowing for the appearance of the object-thing that reveals itself. After having analysed the relationship between design and drawing in text Design through Drawing (Pombo and Magalhães, 2005, 61-72) through the classification of design as a result of the triangulation author-programme-technology and drawing as the interpreter of the concept representation-classification-imagination, we shall analyse the implication of drawing in the project as representation of the idea in the configuration of the object of design. We shall consider the representation through image and the object as reference of the lacanian «thing» (the non represented), searching for the formal differentiation between the image-representation and the object-thing and its relationship in within the subject of design. The structure of argumentation derives from the previous text and is now amplified through two issues: _the first: the implied representation of the concept in the project in design; _the second, in the way the concept manifests itself in the configuration of the object-thing. The study of the relationships between design and drawing is important to the research in design, considering that drawing is a qualification intermediate of the projectual development. The argumentation will be supported by the authors present in the bibliography.